Comparison of the solution and crystal conformations of (G + C)-rich fragments of DNA - Vorlícková, M; Subirana, J A; Chládková, J; Tejralová, I; Huynh-Dinh, T; Arnold, L; Kypr, J (Biophysical journal, 1996)
DNA fragments crystallize in an unpredictable manner, and relationships between their crystal and solution conformations still are not known. We have studied, using circular dichroism spectroscopy, solution conformations of (G + C)-rich DNA fragments, the crystal structures of which were solved in the laboratory of one of the present authors. In aqueous trifluorethanol (TFE) solutions, all of the examined oligonucleotides adopted the same type of double helix as in the crystal. Specifically, the dodecamer d(CCCCCGCGGGGG) crystalized as A-DNA and isomerized into A-DNA at high TFE concentrations. On the other hand, the hexamer d(CCGCGG) crystallized in Z-form containing tilted base pairs, and high TFE concentrations cooperatively transformed it into the same Z-form as adopted by the RNA hexamer r(CGCGCG), although d(CCGCGG) could isomerize into Z-DNA in the NaCl + NiCl2) aqueous solution. The fragments crystallizing as B-DNA remained B-DNA, regardless of the solution conditions, unless they denatured or aggregated. Effects on the oligonucleotide conformation of 2-methyl-2,4-pentanediol and other crystallization agents were also studied. 2-Methyl-2,4-pentanediol induced the same conformational transitions as TFE but, in addition, caused an oligonucleotide condensation that was also promoted by the other crystallization agents. The present results indicate that the crystal double helices of DNA are stable in aqueous TFE rather than aqueous solution.
Keywords: konformace nukleové kyseliny; In Vitro Techniques; cirkulární dichroismus; Nucleic Acid Conformation; DNA; krystalizace; Solutions; Biophysical Phenomena; voda; Oligodeoxyribonucleotides; zastoupení bazí; biofyzikální jevy; roztoky; techniky in vitro; Biophysics; Water; Base Sequence; sekvence nukleotidů; oligodeoxyribonukleotidy; Crystallization; Base Composition; Circular Dichroism; biofyzika; glykoly; Glycols